NAVIGATIONAL CHOICES IN URBAN CONGESTION: A COMPREHENSIVE ANALYSIS OF PASSENGER RIDE INTENTION TOWARDS MOTOR TAXI SERVICES IN MALAYSIA - Abdul Rahim, Fitriya; Tai, Lit Cheng; Goh, Poh Jin; Jaafar Sidik, Morni Hayati (Journal of Sustainable Technology and Applied Science (JSTAS), 2024)
Motorcycles have become a standard mode of transportation in many countries, including Malaysia, due to their affordability, lower fuel consumption, low maintenance costs, and convenience, given the worsening traffic situation. Hence the idea of motorcycle taxis. This concept is common throughout much of Southeast Asia, but the awareness is a novelty in Malaysia, which has depended on cars to act as taxis for some time. Therefore, Malaysia's'motorcycle taxi service’ push has gathered countrywide interest. This study aims to determine factors influencing passenger ride intention towards motor taxis. Data were collected through self-administered questionnaires and online surveys on 206 respondents. SmartPLS analysis generated findings on perceived price, safety, convenience, accessibility, social influence, and ease of use as significant factors in predicting passenger ride intention. The results revealed that there is a substantial relationship between the perceived price, safety, and perceived accessibility towards the intention to use the motor taxi services. This implies that there is a need for the authorities to come up with a policy that protects passenger safety when using this new type of e-hailing service. This research study offers valuable and essential information for stakeholders to understand the psychological determinants further and address the needs of a special interest group of end-users.